STATISTICAL ANALYSIS OF THE ROLE OF INDUSTRIAL ENTERPRISES AND ECONOMIC ACTIVITY IN THE DEVELOPMENT OF THE ECONOMY (Marketing Journal, 2025)
This article analyzes the role of industrial enterprises in the economy and the main difficulties in the process of statistical analysis of their economic activity. The article identifies such problems as lack of information, the level of innovation, finan cial constraints, and the lack of qualified personnel, and proposes effective solutions to them. This study includes practical proposals aimed at ensuring the sustainable development of the industrial sector and strengthening its role in the economy.
Keywords: Industrial enterprises; economic activity; statistical analysis; innovative technologies; financial constraints; qualified personnel; state support; economic development; stability